"Predatory" margins and the regulation and supervision of central counterparty clearing houses (CCPs) - Jan Pieter Krahnen; Loriana Pelizzon (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
This note discusses the basic economics of central clearing for derivatives and the need for a proper regulation, supervision and resolution of central counterparty clearing houses (CCPs). New regulation in the U.S. and in Europe renders the involvement of a central counterparty mandatory for standardized OTC derivatives' trading and sets higher capital and collateral requirements for non-centrally cleared derivatives. From a macrofinance perspective, CCPs provide a trade-off between reduced contagion risk in the financial industry and the creation of a significant systemic risk. However, so far, regulation and supervision of CCPs is very fragmented, limited and ignores two important aspects: the risk of consolidation of CCPs on the one side and the competition among CCPs on the other side. i) As the economies of scale of CCP operations in risk and cost reduction can be large, they provide an argument in favor of consolidation, leading at the extreme to a monopoly CCP that poses the ultimate default risk - a systemic risk for the entire financial sector. As a systemic risk event requires a government bailout, there is a public policy issue here. ii) As long as no monopoly CCP exists, there is competition for market share among existing CCPs. Such competition may undermine the stability of the entire financial system because it induces "predatory margining": a reduction of margin requirements to increase market share. The policy lesson from our consideration emphasizes the importance of a single authority supervising all competing CCPs as well as of a specific regulation and resolution framework for CCPs. Our general recommendations can be applied to the current situation in Europe, and the proposed merger between Deutsche Börse and London Stock Exchange.
urn:nbn:de:hebis:30:3-416899
Keywords: 330; central counterparties; CCP; derivatives; financial market regulation; financial market supervision